Pseudo 3D Imaging of Dielectric and Magnetic Anomalies from GPR Data - Raffaele Persico; Sergio Negri; Francesco Soldovieri; Elena Pettinelli (International Journal of Geophysics)
This paper deals with the reconstruction of buried targets exhibiting both dielectric and magnetic characteristics, starting from GPR data collected at the interface air/soil. The problem is tackled under the Born approximation. In particular, two-dimensional migration and linear inversion results will be compared versus experimental data and three-dimensional representations of the reconstructions achieved from both methods will be shown.